Audit Energi Gedung Rektorat Universitas Sam Ratulangi Manado - Fikri P. Djamaludin; Vecky C. Poekoel; Meita Rumbayan (Universitas Sam Ratulangi, 2018)
Abstract – Consumption of electric energy continues to increase, with the increase in electrical energy needs, the reliability of a power system must also be directly proportional to the needs of electrical energy. Energy audit is a method used to calculate the amount of energy consumption in buildings and recognize ways to save.The energy audit at Sam Ratulangi University of Manado, North Sulawesi Rectorate building aims to know the energy usage and energy utilization conditions and energy saving opportunities in the Rectorate Building of Universitas Sam Ratulangi Manado, North Sulawesi.From the data obtained there are some buildings / rooms that have not met the criteria and there are also rooms that meet the criteria of energy audits. And from this analysis used planning to optimize the use of electric energy and other energy utilization in Rectorate Building of University of Sam Ratulangi Manado, North Sulawesi to be more economical and support program of University of Sam Ratulangi to be better. Keywords – Energy Audit, Electrical Energy, Energi Audit Analysis, Rectorate Building Of Sam Ratulangi Of Manado, Abstrak – Konsumsi akan energy listrik terus meningkat, dengan peningkatan kebutuhan energi listrik maka keandalan suatu sistem tenaga listrik juga harus berbanding lurus dengan kebutuhan energi listrik. Audit energi adalah metode yang dipakai untuk menghitung besarnya konsumsi energi pada bangunan gedung dan mengenali cara – cara untuk penghematannya.Audit energi di gedung Rektorat Universitas Sam Ratulangi Manado, Sulawesi Utara bertujuan untuk mengetahui penggunaan energi dan Kondisi pemanfaatan energi serta peluang penghematan energi di gedung Rektorat Universitas Sam Ratulangi Manado, Sulawesi Utara. Dari data yang diperoleh ada beberapa bangunan/ruangan yang belum memenuhi kriteria. Dan dari analisa ini digunakan perencanaan untuk mengoptimalkan penggunaan energi listrik serta pemanfaatan energi lain di gedung Rektorat Universitas Sam Ratulangi Manado, Sulawesi Utara agar dapat lebih ekonomis dan mendukung program Universitas Sam Ratulangi menjadi lebih baik.Kata Kunci – Audit Energi, Analisa Audit Energi, Energi Listrik, Gedung Rektorat Universitas Sam Ratulangi Manado,